POLITICAL PARTIES IN THE INDONESIAN POLITICAL SYSTEM AFTER THE ROLLING OF REFORMS - Muhammad Budiana; Willya Achmad (Fox Justi : Jurnal Ilmu Hukum, 2022)
Since Indonesia's independence until the reformation of the Indonesian nation, the country's political system has not been one that is purely derived from the socio-cultural values of the Indonesian nation itself, but rather one that utilizes the political culture of the Dutch colonial government. This has been the case from the time of Indonesia's independence until the nation's reformation. The existence of political parties in Indonesia is also impacted as a result of this. The purpose of this study is to investigate the roles that political parties have played in Indonesia's political system since the country's recent reforms. In this investigation, a qualitative strategy is combined with a descriptive research approach. The findings of the study indicate that after the reform in Indonesia, political parties are not able to properly function as pillars of democracy in the political system in Indonesia. Instead, political parties in Indonesia prefer to sacrifice their party ideology, which is the defining characteristic of the party, in order to simply receive the highest number of votes possible. Because of this, political parties in Indonesia exhibit the characteristics of floating parties.